Karakteristik Kebijaksanaan Menurut Al-Qur’an: Studi Komparasi Tafsir Al-Azhar dan Tafsir Al-Misbah - Khanif, Moch. Fahmi; Iqbal, Ipmawan Muhammad; Murdianto, Murdianto (Adh Dhiya | Journal of The Quran and Tafseer Studies, 2024)
The memorization of wisdom in the Qur'an is mostly addressed to prophets and apostles, namely wisdom which means al-Sunnah, knowledge of halal and haram, about secrets that are not known to ordinary people. Based on the background that has been described above, the author is interested in further examining the comparison of the interpretation of the meaning of wisdom in Tafsir Al-Azhar and Tafsir Al-Misbah. This research aims so that we can know the meaning of wisdom and know the differences and similarities in the interpretation of the meaning of wisdom in Al-Azhar and Al-Misbah commentaries. This research uses library research method, which is by collecting data and information related to wisdom. The data analysis technique used in this research is qualitative with muqarin (comparative) approach. The result of this research is Hikmah, which means wisdom. There is only one similarity in the interpretation of wisdom according to Buya Hamka and M. Qurash Shihab, namely, interpreting that what is meant by wisdom in the verse is the prophethood of prophet David and the book revealed to him, as well as the miracles that accompany it. The difference in interpretation between the two mufassirs explains the secrets of this life to the ummah and is the science of practice and scientific deeds, among others what is listed in the books of the taurat and the gospel.